2010
DOI: 10.1007/s11033-010-0288-7
|View full text |Cite
|
Sign up to set email alerts
|

Fbxw8 is involved in the proliferation of human choriocarcinoma JEG-3 cells

Abstract: Fbxw8 is the F-box component of a SCF-like E3 ubiquitin ligase complex. Mice lacking Fbxw8 exhibit pathological defects in placenta and embryo similar to fetal growth retardation, suggesting a role of Fbxw8 in placentation. Proliferative capacity of trophoblast cells is very important in placental development. In this context, we revealed that Fbxw8 was expressed in four different human trophoblast cell lines. Silencing of Fbxw8 expression by siRNA inhibited the growth of choriocarcinoma JEG-3 cells. By Wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…An increasing volume of data has revealed the role of Fbxw8 E3 ligase in cancer (20,21,28,29). Impaired proliferation kinetics was identified in the Fbxw8 -/-mouse embryonic fibroblasts (30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increasing volume of data has revealed the role of Fbxw8 E3 ligase in cancer (20,21,28,29). Impaired proliferation kinetics was identified in the Fbxw8 -/-mouse embryonic fibroblasts (30).…”
Section: Discussionmentioning
confidence: 99%
“…It was also revealed that miR-3160-5P inhibited DU145 cell proliferation by targeting Fbxw8. Target-inhibition of Fbxw8 arrested cell cycle progression at the G 2 /M phase in choriocarcinoma JEG3 cells by decreasing the expression level of G 2 /M-associated cell cycle regulators and increasing the expression level of p27 (20,21). The in-depth molecular mechanisms underlying cell cycle arrest induced by miR-3160-5P were investigated further.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, mTOR complex 2 (mTORC2) was recently found to phosphorylate and subsequently stabilize FBXW8, leading to accelerated turnover of insulin receptor substrate 1 (IRS1) 49 . Moreover, it has been reported that FBXW8 negatively regulated cancer cell proliferation through proteolysis of cyclin D1 (REFS 50,51) (see Supplementary information S2 (table)). Nonetheless, tissue-specific knockout mouse models and identification of additional FBXW8 substrates are necessary to determine whether FBXW8 has a crucial role in suppressing tumorigenesis.…”
Section: Tumour-suppressive F-box Proteinsmentioning
confidence: 99%
“…This is the only example where failure to degrade cyclin D1 was shown to increase its abundance, and was associated with growth inhibition instead of growth stimulation. Suppressed growth following FBXW8 depletion was also seen in the human choriocarcinoma JEG-3 cells, and this was associated with cell cycle arrest in G2/M phase with concurrent upregulation of the p27 protein [268]. Whether cyclin D1 plays a role in this growth suppression remains to be investigated.…”
Section: F-box Proteins With Tumor-suppressive Propertiesmentioning
confidence: 99%